The impact of school transitions from mono-ethnic to mixed-ethnic schools for adolescents in Vukovar, Croatia - Merrilees, Christine E. (2013)
School transitions bring changes such as the reorganization of social groups and the opportunity to make new friends. In segregated communities with histories of inter-ethnic conflict, these same transitions also bring tension and increased ethnic awareness to youth who have had little or no prior contact with other group members (Stephan & Stephan, 2005). These perceptions of tension and greater awareness of identity have been linked with increased tendency to discriminate against ‘other’ group members (Nesdale, Maass, Durkin, & Griffiths, 2005). The current study examines the role of perceived intergroup tension and strength of social identity on youths’ tendency to discriminate for youth transitioning from mono-ethnic primary schools to mixed-ethnic secondary schools in Vukovar, a divided society in Croatia along the border with Serbia devastated during the dissolution of the Former Yugoslavia. This paper uses path analysis to examine majority/minority differences to show how the increase in inter-ethnic tension and social identity contribute to out-group discrimination. The results are based on 230 self-reports from Croat and Serb youth in primary and secondary schools in Vukovar. The results suggest that compared to primary school students, secondary school students perceive more inter-ethnic tension and report higher levels of identification with their social group ; both social identity and perceived intergroup tension were related to greater likelihood of discriminating against out-group members. However, differences between Croat (majority) and Serb (minority) youth emerged. The findings have implications for school and educational policies in ethnically-diverse contexts.